1998
DOI: 10.1097/00019048-199802000-00005
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Randomized Study Comparing the Efficacy and Safety of Intravenous and/or Oral Levofloxacin versus Ceftriaxone and/or Cefuroxime Axetil in Treatment of Adults with Community-Acquired Pneumonia

Abstract: Five hundred ninety patients were enrolled in a prospective, multicenter, randomized trial comparing the efficacy and safety of 7 to 14 days of levofloxacin treatment with that of ceftriaxone and/or cefuroxime axetil in the management of community-acquired pneumonia in adults. Patients received either intravenous and/or oral levofloxacin (500 mg once daily) or the comparative agents, parenteral ceftriaxone (1 to 2 g once to twice daily) and/or oral cefuroxime axetil (500 mg twice daily). Erythromycin or doxycy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
126
0
11

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(143 citation statements)
references
References 15 publications
6
126
0
11
Order By: Relevance
“…These studies usually have reported clinical cure rates Ͼ90%. 4,5 For levofloxacin, cure rates in mild to moderate CAP have ranged from 94% to 98%, 4,5,32 and in severe disease, 87%. 33 These studies have shown that levofloxacin compares favorably with ceftriaxone.…”
Section: Fluoroquinolone Efficacy In Community-acquired Pneumoniamentioning
confidence: 99%
See 3 more Smart Citations
“…These studies usually have reported clinical cure rates Ͼ90%. 4,5 For levofloxacin, cure rates in mild to moderate CAP have ranged from 94% to 98%, 4,5,32 and in severe disease, 87%. 33 These studies have shown that levofloxacin compares favorably with ceftriaxone.…”
Section: Fluoroquinolone Efficacy In Community-acquired Pneumoniamentioning
confidence: 99%
“…Two trials 32,33 of IV-PO switch therapy compared levofloxacin with ceftriaxone followed by PO cephalosporin therapy. One study, 32 a large series in predominantly ambulatory patients (half initially treated in the hospital), reported clinical success at 1 week after therapy in 96% of patients receiving levofloxacin (217/ 226), compared with 90% after cephalosporin therapy (ceftriaxone/cefuroxime axetil) (207/230).…”
Section: Fluoroquinolone Efficacy In Community-acquired Pneumoniamentioning
confidence: 99%
See 2 more Smart Citations
“…Bradley et al [5] in their comparative study of levofloxacin in the treatment of children with community-acquired pneumonia showed that cure rate of levofloxacin was 94.3% whereas cure rate of comparator group (0.5 to <5 years: amoxicillin/ clavulanate or ceftriaxone; > or =5 years: clarithromycin or ceftriaxone with clarithromycin or erythromycin lactobinate) was 94%. File et al [12] in their comparative study of intravenous and/or oral levofloxacin (500 mg once daily) or the comparative agents, parenteral ceftriaxone (1 to 2 g once to twice daily) and/or oral cefuroxime axetil (500 mg twice daily) in treatment of adults with community-acquired pneumonia showed that clinical success rate of levofloxacin (96%) is superior to ceftriaxone and/or cefuroxime axetil (90%) in the management of adult with CAP. Cure rate of levofloxacin in these mentioned studies support the present study.…”
Section: Discussionmentioning
confidence: 99%